Morning headache in sleep apnea and the response to continuous positive airway pressure treatment: a systematic review - Knorst, Gabriel Rocha Santos; Borges, Beatriz Santana (Headache Medicine, 2026)
IntroductionThere is a strong association between Obstructive Sleep Apnea (OSA) and headache. Recently, morning headache has been suggested as part of the clinical findings of OSA, and is currently listed in the third edition of the International Classification of Headache Disorders under the title sleep apnea headache. It is defined as recurrent morning headache with an Apnea-Hypopnea Index (AHI) greater than or equal to 5, verified by polysomnography, and headache cessation within 72 hours of effective sleep apnea treatment. The use of continuous positive airway pressure (CPAP) for the treatment of OSA and, consequently, for morning headache, is well established, although some studies do not demonstrate this association.ObjectiveThe objective of this study is to systematically review the evidence on the effectiveness of CPAP in the treatment of morning headache in individuals with sleep apnea syndrome, observing the headache characteristics, side effects, and benefits of therapy.MethodsThis is a systematic review of scientific articles published up to June 2024 using the electronic platforms: PubMed, Cochrane Library, SciELO, and LILACS.ResultsOf the 308 articles found, seven studies were selected because they met the inclusion criteria. The selected articles include one randomized clinical trial, four prospective observational studies, one cross-sectional study, and one retrospective study. All articles highlighted the relationship of morning headache as a common symptom in patients with OSA and demonstrated some degree of symptom improvement after CPAP treatment.ConclusionsThis systematic review demonstrates a growing body of evidence consistently supporting the beneficial effect of CPAP in the treatment of morning headache in patients with OSA. Given the potential presented, but limited by the scarcity of high-quality articles, more controlled studies are needed to establish and standardize the clinical use of the method for this purpose.